1985
DOI: 10.1007/bf01893120
|View full text |Cite
|
Sign up to set email alerts
|

Predictive relationship of hiatal hernia to reflux esophagitis

Abstract: The relationship between hiatal hernia and reflux esophagitis was compared in 93 patients who underwent both radiographic and endoscopic examination of the esophagus. In 46 patients with a normal esophagus shown endoscopically, hiatal hernia was present in 59%, while 94% of 47 patients with reflux esophagitis had hiatal hernia. The positive and negative predictive values for hiatal hernia in diagnosing or excluding esophagitis were 62% and 86%, respectively. Extrapolation of these data and review of the litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(39 citation statements)
references
References 24 publications
3
36
0
Order By: Relevance
“…The mean total esophageal exposure to acid was 4.8% in patients with minimal hiatal hernias and 6.6% in those with larger hiatal hernias. we found that 94% of patients with neflux esophagitis had hiatal hernia in a population with a 51% prevalence of disease [1]. The positive predictive value of hiatal hernia in patients with reflux esophagitis was 62%, and the negative predictive value of the absence of hernia in excluding esophagitis was 86%.…”
Section: Resultsmentioning
confidence: 69%
“…The mean total esophageal exposure to acid was 4.8% in patients with minimal hiatal hernias and 6.6% in those with larger hiatal hernias. we found that 94% of patients with neflux esophagitis had hiatal hernia in a population with a 51% prevalence of disease [1]. The positive predictive value of hiatal hernia in patients with reflux esophagitis was 62%, and the negative predictive value of the absence of hernia in excluding esophagitis was 86%.…”
Section: Resultsmentioning
confidence: 69%
“…However, in order to demonstrate the relative positions of the EGJ and the diaphragmatic hiatus, the positions of these structures must be visible radiograpically, which means the esophagus must be distended with consequent shortening and displacement of the EGJ as discussed above. Recognition of this confounding effect led to the 2 cm rule wherein there must be more than 2 cm separation between the B ring and the diaphragmatic hiatus before being considered a sliding hiatus hernia ( Figure 5) [15]. Lesser magnitudes of separation are attributed to physiologic herniation.…”
Section: The Radiographic Assessment Of Sliding Hiatus Herniamentioning
confidence: 99%
“…A strong association has been described between the presence of a hiatus hernia and Barrett’s esophagus [13,28,29,30,31,32], with a 2-cm or longer hernia found in 96% of 46 patients with Barrett’s esophagus [31]. Hiatal hernia impairs LES function [33], and the resultant lower LES pressure increases susceptibility to reflux events [34, 35].…”
Section: Hiatal Herniamentioning
confidence: 99%